2022
DOI: 10.1177/17590914221121257
|View full text |Cite
|
Sign up to set email alerts
|

In UteroExposure to Zika Virus Results in sex-Specific Memory Deficits and Neurological Alterations in Adult Mice

Abstract: Transplacental transmission of Zika virus (ZIKV) during early pregnancy may lead to several neurological alterations, known as congenital Zika syndrome. We have previously shown that intravaginal infection of immunocompetent dams with ZIKV during the early stage of pregnancy triggers neuroinflammation in fetuses, characterized by increased brain expression of inflammatory factors, including IL-6, IL-18, CCL2, CXCL1, and CXCL10. The present study sought to understand the long-term consequences of these early ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 75 publications
2
10
0
Order By: Relevance
“…A previous study by our group showed that maternal exposure to ZIKV affects placental function, including placental ultrastructure and ABC transporter protein expression, even in the absence of vertical transmission and that these effects are dependent on viral infective titers and maternal immune status (Andrade et al, 2021). Despite their importance to fetal growth and development and their role in response to infections, there is limited information about GLUT and SNAT transporter expression profiles and OGT nutrient-sensing pathway activity in the placenta of ZIKV-infected dams.…”
Section: Hbp and O-glcnacylation Are Central In Controlling Immune Ce...mentioning
confidence: 89%
See 4 more Smart Citations
“…A previous study by our group showed that maternal exposure to ZIKV affects placental function, including placental ultrastructure and ABC transporter protein expression, even in the absence of vertical transmission and that these effects are dependent on viral infective titers and maternal immune status (Andrade et al, 2021). Despite their importance to fetal growth and development and their role in response to infections, there is limited information about GLUT and SNAT transporter expression profiles and OGT nutrient-sensing pathway activity in the placenta of ZIKV-infected dams.…”
Section: Hbp and O-glcnacylation Are Central In Controlling Immune Ce...mentioning
confidence: 89%
“…The i.v. injections were performed at GD12.5, and virus preparation was undertaken as previously described (Coelho et al, 2017;Andrade et al, 2021). At 18.5, all animals were weighed and euthanized with 5% isoflurane by inhalation.…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations